The Effect of using the constructivist learning model on acquiring historical concepts among middle school students and their attitudes towards the subject - Majeed, Fouad Hamid (Journal of Tikrit University for Humanities, 2020)
The aim of the research is to identify the effect of using the constructivist learning model on acquiring historical concepts among middle second grade students and their attitudes towards the subject. To verify this goal, the researcher adopted semi-experimental design with partial control with two (experimental and control) groups with the post test. ) A student of the experimental group and (29) a student of the control group, and equivalence was carried out between the two groups with a number of variables. Suitable for the purpose of analyzing statistical data such as averages and deviations (t.test), for two independent samples equivalent (Kuder Richardson 20), and Pearson correlation coefficient and found that there is a statistically significant difference at the level of significance (0.05) and a degree of freedom (57) between the averages in favor of the experimental group in a test The acquisition of historical concepts and the measure of the trend towards the material, and from that the researcher concluded that there is a positive effect of using the constructive learning model in teaching historical concepts for students and the trend towards the material, and based on these results the researcher put some suggestions and recommendations.